Influence of Information System Factors to Operational Performance Sustainability of UAE Manufacturing Sector - Darwish Abdulla Lari, Darwish Ahmed; Darwish Lari, Fatima Ahmed; Darwish Abdulla Lari, Mohamed Ahmed (International Journal of Sustainable Construction Engineering and Technology, 2020)
This paper presents an assessment of information system factors that influence the operational performance sustainability of UAE manufacturing sector. The study was conducted using quantitative approach where data was collected through the questionnaire survey and analysed statistically. A total of 41 factors of information system extracted from literature review and clustered into 4 domains namely transaction processing system; operation information system; decision support system and financial manager’s workbench. The survey distributed 250 questionnaires among operations staff of UAE manufacturing industries. However, only 200 datasets were considered valid for further analysis. Ranking of factors were conducted using mean score and standard deviation. The results found that the most influential domain is decision support system having mean value of 4.19. The findings from this study give an indicator on the importance of information system toward the sustainable operational performance of the UAE manufacturing sector